Training on Making Financial Reports among Teachers and Students Participating in Online-Based Teaching Campus MBKM - Deni Sunaryo; Yoga Adiyanto; Ahmad Firdaus (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
This community service activity program seeks to teach teachers and students participating in the Teaching Campus MBKM the basics of preparing financial reports. Teachers and students in elementary schools need a basic understanding of the preparation of financial reports to apply the theories learned at school. Training from Lecturers to Teachers and Students at SDN 131 Cijawura and SDN 027 Cicadas Bandung City is the method applied in this community service project. Indonesia's situation is still in the COVID-19 pandemic since March 2020 President Joko Widodo informed that many Indonesian people have contracted COVID-19 until the community service activities were carried out on March 5 2023, the counseling was carried out via zoom sessions. The teachers and students who are currently implementing the government program, namely the Teaching Campus MBKM at SDN 131 Cijawura and SDN 027 Cicadas Bandung City clearly understand the subjects taught by the lecturers, seen from the excitement with which these questions are answered during this counseling activity. This activity is expected to help teachers and students understand how to record and make reports so that they can successfully adapt when entering society and make accountability reports for the MBKM Campus Teaching activities.